Reliability assessment for liquefied natural gas ship's distributed control system [electronic resource] - Arulhaizal Adam Hamzah, 1977- (2011)
Thesis (Sarjana Kejuruteraan (Mekanikal - Teknologi Marin)) - Universiti Teknologi Malaysia, 2011